Montreal Convention and its Applicability in India: Examining the Impact of Montreal Convention on Consumer Rights in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
India became 91st country to ratify the Convention for Unification of Certain Rules forInternational Carriage by Air done at Montreal on 28th May, 1999 in the year 2009. The Montreal Convention,1999 has been incorporated into the Carriage by Air (Amendment) Act, 2009 in India and is said to havebrought pro-consumer move. It, therefore, needs to be understood whether the move from pro-carrier topro-consumer has actually occurred in the Indian landscape after incorporation of the principles ofMontreal Convention under the Indian laws. The paper aims to discuss the reason for which MontrealConvention, 1999 came into being and circumstances that why the convention was adopted in India. Thearticle also analyse that whether Montreal Convention, 1999 has successfully brought a pro-consumerregime in the Indian landscape? The Montreal Convention (formally, the Convention for the Unification ofCertain Rules for International Carriage by Air) is a multilateral treaty adopted by a diplomatic meeting ofICAO member states in 1999. The provisions of the Montreal Convention, 1999 have been incorporated inthe Indian carriage laws as well which help in providing greater certainty for passengers and carriers interms of their respective rights and liabilities in the event of an accident involving international carriage.Therefore, the incorporation of the principles of Montreal Convention, 1999 under the Indian air carriagelaws has been a successful move from a regime that favoured carriers to a regime that has now becomepro-consumer.